Knowledge of God Almighty according to Sheikh Muhammad Al-Amin Al-Harari (may God have mercy on him (Islamic Sciences Journal, 2024)
ABSTRACTThe first goal of all religion is to introduce  Allah  Almighty, as it is not right for a person to worship a Lord whom he does not truly know, and the Islamic sects differed regarding this knowledge. Some of them said: looking, and among them were those who said: the intention is to look, and among them were those who said: other than That, and Sheikh Al-Harari (may  Allah  have mercy on him) said: Knowledge of  Allah  cannot be attained except by Sharia law and that is through revelation, not by human machines of reason and otherwise, and that there is no life for souls except by knowledge of Allah Almighty.
Keywords: Knowledge, God, at, Sheikh, Muhammad, Al-Amin, Al-Harari.